Autism: understanding alternative, complementary, and emerging treatments - Volkmar, Fred (Henry Stewart Talks, 2021)
History of autism, Evidence based practice, Treating autism, Emerging treatments in autism, Complementary and alternative treatments, Disproven autism treatments, Chelation treatments in autism, Secretin